Structure- and Ligand-Based Virtual Screening for Identification of Novel TRPV4 Antagonists - Atefeh Saadabadi; Linda Wilkman; Marja Rantanen; Ari-Pekka Koivisto; Outi M. H. Salo-Ahen (Molecules)
Transient receptor potential vanilloid (TRPV) 4 is involved in signaling pathways specifically mediating pain and inflammation, making it a promising target for the treatment of various painful and inflammatory conditions. However, only one drug candidate targeting TRPV4 has entered the clinical trials. To identify potential TRPV4 inhibitors for drug development, we screened a library of ion channel-modulating compounds using both structure- and ligand-based virtual screening approaches. Since a high-resolution experimental structure of the human TRPV4 (hTRPV4) was not available during this study, we used a comparative model of hTRPV4 for the structure-based screening by molecular docking. The ligand-based virtual screening was performed using the pharmacophoric features of two known TRPV4 antagonists. Five potential hits were selected based on either the binding stability or the pharmacophore match, and their effect on hTRPV4 was tested using a FLIPRtetra assay. All tested compounds inhibited hTRPV4 at 30 µM, with compound Z1213735368 showing an IC50 of 8 µM at a concentration of 10 µM. Furthermore, natural stilbenoids, known to modulate other TRP channels, were evaluated for their hTRPV4 binding and inhibitory potential. The findings provide insight into the structural determinants of hTRPV4 modulation and may facilitate further efforts in developing therapeutic hTRPV4 ligands.